Estimates of Skipped Spawning in Lean and Siscowet Lake Trout in Southern Lake Superior: Implications for Stock Assessment. Issue 3 (29th April 2014) - Sitar, Shawn P.; Jasonowicz, Andrew J.; Murphy, Cheryl A.; Goetz, Frederick W.
Abstract: We found that some lean (12.2%) and siscowet (58.0%) Lake Trout Salvelinus namaycush in populations in southern Lake Superior do not reproduce each year (i.e., display "skipped spawning") even though they have reached puberty. We measured skipped spawning in Lake Trout in southern Lake Superior and assessed its impact on reproduction by developing length‐based and age‐based ogives (i.e., probabilities of being mature). In populations in which skipped spawning is negligible, a maturity ogive can be considered equivalent to a reproduction ogive (probability of being reproductive). However, in populations in which skipped spawning is present, such as in lean and siscowet Lake Trout in southern Lake Superior, maturity and reproduction ogives are very different. We evaluated the influence of skipped spawning on a key stock assessment quantity—spawning stock biomass—by applying maturity and reproduction ogives to simulated populations. Furthermore, we evaluated whether skipped spawning was associated with lower energy reserves by testing for differences in the hepatosomatic index (HSI) according to maturity status. Our population simulations indicate that spawning stock biomass can be overestimated (8.3% for leans and 475% for siscowets) when skipped spawners are assumed to be a part of the spawning stock. An inflated reproductive potential of the population could allow for excessive fishing if quotas are based on these biased spawning stock biomass estimates. Siscowet Lake Trout that were skipping spawning had significantly lower energy reserves (assessed by HSI) than mature fish. The high incidence of skipped spawning in siscowets may be related to the reported slowed somatic growth, high population abundance, and low prey resources in southern Lake Superior, which supports the hypothesis that skipped spawning is a density‐dependent response to limited energy resources.